Treatment of plantar fasciitis by LowDye taping and iontophoresis: short term results of a double blinded, randomised, placebo controlled clinical trial of dexamethasone and acetic acid. - Osborne, H.; Allison, Garry (BMJ Publishing Group, 2006)
Objectives: To determine if, in the short term, acetic acid and dexamethasone iontophoresis combined with LowDye (low-Dye) taping are effective in treating the symptoms of plantar fasciitis. Methods: A double blinded, randomised, placebo controlled trial of 31 patients with medial calcaneal origin plantar fasciitis recruited from three sports medicine clinics. All subjects received six treatments of iontophoresis to the site of maximum tenderness on the plantar aspect of the foot over a period of two weeks, continuous LowDye taping during this time, and instructions on stretching exercises for the gastrocnemius/soleus. They received 0.4% dexamethasone, placebo (0.9% NaCl), or 5% acetic acid. Stiffness and pain were recorded at the initial session, the end of six treatments, and the follow up at fourweeks. Results: Data for 42 feet from 31 subjects were used in the study. After the treatment phase, all groups showed significant improvements in morning pain, average pain, and morning stiffness. However for morning pain, the acetic acid/taping group showed a significantly greater improvement than the dexamethasone/taping intervention. At the follow up, the treatment effect of acetic acid/taping and dexamethasone/taping remained significant for symptoms of pain. In contrast, only acetic acid maintained treatment effect for stiffness symptoms compared with placebo (p = 0.031) and dexamethasone. Conclusions: Six treatments of acetic acid iontophoresis combined with taping gave greater relief from stiffness symptoms than, and equivalent relief from pain symptoms to, treatment with dexamethasone/taping. For the best clinical results at four weeks, taping combined with acetic acid is the preferred treatment option compared with taping combined with dexamethasone or saline iontophoresis.